The Effectiveness Project Work Teaching Techniques Of Sakubun Teaching Collaboration With Kaiwa - Aan Amalia; Raden Novitasari (WIDAI Japanese Journal, 2020)
This research is focused on collaborative learning between sakubun (writing) and kaiwa (speaking) subjects. In the subjects of sakubun and kaiwa, the teacher must look for the right teaching method or technique so that the teaching and learning process is not monotonous and boring for learners. In sakubun courses, the teacher must have thoroughness in terms of examining the results of student writing and having insight into vocabulary and culture. Whereas in speaking courses (kaiwa), the teacher must have creativity in preparing the teaching material and techniques because of the teaching that all learners are required to actively speak. The ultimate goal of teaching Japanese is so that learners are able to communicate their ideas or ideas using Japanese both verbally and in writing. The methods and techniques used in learning are thematic methods with the technique of teaching project work. The purpose of this study is to provide a renewal in the teaching pattern of the sacred and kaiwa so that it can improve the effectiveness of teaching and the ability of students in writing and speaking is expected to increase. Collaborating writing (sakubun) and speaking (kaiwa) courses is one of the treatments carried out by the author to create a learning environment that is not boring. From the results of data processing, it can be concluded that collaboration between teaching writing and teachingspeaks using project work techniques is quite effective to improve student achievement. in addition to teaching using project work techniques, learners also get a pleasant learning experience.